<h3>
♫ - - - - - - - - - - - - - - - ~Hello There!~ - - - - - - - - - - - - - - - ♫</h3>
➷ Just substitute 3 in:
2(3)^2 = 18
It would be 18
<h3><u>✽</u></h3>
➶ Hope This Helps You!
➶ Good Luck (:
➶ Have A Great Day ^-^
↬ ʜᴀɴɴᴀʜ ♡
Answer:
y =
(x - 5)² - 2
Step-by-step explanation:
The equation of a parabola in vertex form is
y = a(x - h)² + k
where (h, k) are the coordinates of the vertex and a is a multiplier
Here (h, k) = (5, - 2), thus
y = a(x - 5)² - 2
To find a substitute (7, 0) into the equation
0 = a(7 - 5)² - 2
0 = 4a - 2 ( add 2 to both sides )
2 = 4a ( divide both sides by 4 )
a =
= ![\frac{1}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D)
y =
(x - 5)² - 2 ← in vertex form
Answer:
One approach to this problem is to obtain the graph for the given equation.
We need to find every intersection those functions have with the axis 'x' and 'y'
starting with g(x)
g(x=0)=0-3, first point (0,-3) it iis the crossing point with 'x' axis
g(x)=0=x-3, second point (3,0) it iis the crossing point with 'y' axis
Lets do the same for f(x)
g(x=0)=0, this leads to the first point (0,0) it iis the crossing point with 'x' axis and also, with the 'y' axis
We dont need to find any other, since always y=x
By plotting we have the attached picture
Now you can see that g(x) differs from its parent function in that is shifted 3 units to the right, and also 3 units down.
Step-by-step explanation:
Answer:
is there a picture?
Step-by-step explanation:
<span>No, it doesn't. To find out if it's a right angled triangle, we use Pythagorean triple. It states that the square of the hypotenuse (the longest side) is equal to the sum of the squares of the opposite and adjacent sides. Obviously, the longest side, which is our hypotenuse is 24. So we want to find out whether the square of our hypotenuse is equal to the sum of the squares of the other two sides i. e 13 and 21.
24^ 2 = 576 ; 13^2 = 169 ; 21^2 = 441;
So is 576 = 169 + 441. An emphatic No: hence the triangle isn't right angled since it doesn't satisfy pythagorean triple.. A^2 is not equal to B^2 + C^2 where a is the hypotenuse and b and c the opposite and adjacent sides.</span>